Effects of local vanadium delivery on diabetic fracture healing. Issue 10 (8th March 2017) - Ippolito, Joseph A.; Krell, Ethan S.; Cottrell, Jessica; Meyer, Ryan; Clark, Devin; Nguyen, Daniel; Sudah, Suleiman; Muñoz, Maximillian; Lim, Elisha; Lin, Anthony; Lee, Thomas Jae Hoon; O'Connor, James Patrick; et al.
ABSTRACT: This study evaluated the effect of local vanadyl acetylacetonate (VAC), an insulin mimetic agent, upon the early and late parameters of fracture healing in rats using a standard femur fracture model. Mechanical testing, and radiographic scoring were performed, as well as histomorphometry, including percent bone, percent cartilage, and osteoclast numbers. Fractures treated with local 1.5 mg/kg VAC possessed significantly increased mechanical properties compared to controls at 6 weeks post‐fracture, including increased torque to failure (15%; p  = 0.046), shear modulus (89%; p  = 0.043), and shear stress (81%; p  = 0.009). The radiographic scoring analysis showed increased cortical bridging at 4 weeks and 6 weeks (119%; p  = 0.036 and 209%; p  = 0.002) in 1.5 mg/kg VAC treated groups. Histomorphometry of the fracture callus at days 10 and 14 showed increased percent cartilage (121%; p  = 0.009 and 45%; p  = 0.035) and percent mineralized tissue (66%; p  = 0.035 and 58%; p  = 0.006) with local VAC treated groups compared to control. Additionally, fewer osteoclasts were observed in the local VAC treated animals as compared to controls at day 14 (0.45% ± 0.29% vs. 0.83% ± 0.36% of callus area; p  = 0.032). The results suggest local administration of VAC acts to modulate osteoclast activity and increase percentage of early callus cartilage, ultimately enhancing mechanical properties comparably to non‐diabetic animals treated with local VAC. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2174–2180, 2017.